If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -30 = x + -25 Reorder the terms: -30 + 6x = x + -25 Reorder the terms: -30 + 6x = -25 + x Solving -30 + 6x = -25 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -30 + 6x + -1x = -25 + x + -1x Combine like terms: 6x + -1x = 5x -30 + 5x = -25 + x + -1x Combine like terms: x + -1x = 0 -30 + 5x = -25 + 0 -30 + 5x = -25 Add '30' to each side of the equation. -30 + 30 + 5x = -25 + 30 Combine like terms: -30 + 30 = 0 0 + 5x = -25 + 30 5x = -25 + 30 Combine like terms: -25 + 30 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 9g-15=21 | | 3.4x=1.8x+2.5 | | 5x-6+2x=9x-7 | | 9j^2+42j+49=0 | | 3x^2+15x-9.1=0 | | h=3(1)+1 | | 0.2c+0.08c-3.6c=0 | | 9=9-11x | | 0.3(y+2)=24 | | 10z^2-1440=0 | | 28-2u=5u | | 2x+14=-5x-11 | | -5/4m-1/6=7/3 | | 4x-2=7-2x | | 8+3x-9x=20 | | 0=1-x+y | | 12x+3x-7=4x+31 | | 3x+3*(-3)=3 | | 5x+8+x=170 | | h=3(0)+1 | | 3x+3*3=3 | | -16h^2-49h-3=0 | | h=3(-2)+1 | | 3*(-2)+3y=3 | | h=3(-1)+1 | | .3(3z+7)+18.9=.5(3z-6) | | 5km+3=77km | | y-4=-x-1 | | 8-18=38 | | 8-4x=4-(2x+6) | | 9(2z+4)=-23 | | 3(6x+8)=11x-5 |